The effect of marital status on stage at diagnosis and survival in Saudis diagnosed with colorectal cancer: cancer registry analysis - Alyabsi, Mesnad (Sci Rep, 2021)
Colorectal cancer (CRC) is the most common cancer in males and third in females in Saudi Arabia, with the majority (66%) diagnosed at a late stage. We evaluated the effect of marital status on stage at diagnosis and CRC survival. We hypothesized that married patients would be more likely to present at an early stage and have higher survival than unmarried patients. The Ministry of National Guard-Health Affairs (MNG-HA) cancer registry was used to identify patients diagnosed with CRC from 2009 to 2017. A competing risk analysis was performed to assess the 5-year CRC-specific survival, adjusting for potential confounders. The Kaplan–Meier method and the Cox regressions were used to assess survival. Two-thirds (76.50%) of the 936 CRC patients were married, 11.64% were unmarried, and 11.86% had an unknown marital status. With multiple imputation-based analysis, the multivariate analysis indicated that unmarried patients were 52% more likely to present at an advanced stage [adjusted odds ratio (aOR) 1.52; 95% CI 1.33–1.73], and had a 30% higher risk of death due to CRC compared to the married patients (aHR 1.30; CI 1.17, 1.44). Future CRC screening and survivorship programs should assess the needs of the vulnerable unmarried population. Interventions supporting the early detection of CRC in this population may be beneficial in the long term and lead to improved cancer outcomes.